Jeremy Bentham i rządy graczy w pchełki, czyli rzecz o tym, że nie każdy liberał jest liberalny (Politeja, 2017)
Jeremy Bentham and the Tiddlywinks Player Rules, That Is About That Not Every Liberal Is LiberalJeremy Bentham is one of the most important Anglo‑Saxon political thinkers, jurists, social reformers and founders of utilitarianism. He also deserves a prominent position in the history of democratic ideas. Bentham not only perceived popular rule as a vehicle for the materialisation of his vision of utilitarian society, but he also gave us a detailed picture of the basic institutions of that form of democracy. In this article the Author suggests that Benthamiam political concept is not liberal but radical and also rooted in continental radical philosophy of French Enlightenment. By rejecting classical liberal ideas such as natural rights, law of nature, social contract and limited government he opened the door for the democratic tyranny of mediocrity justified by the victory of equality over liberty.